Implementation of Islamic Education Leadership and Clinical Supervision on Teacher Performance at MA Nahdlatul Wathan Licin Banyuwangi - Lailatusolihah, Lailatusolihah; Jayanti, Deasy Rolla; Zuhriyah, Indah Aminatus (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study aims to analyze the implementation of Islamic educational leadership and clinical supervision on teacher performance at MA Nahdlatul Wathan Licin Banyuwangi. Using a qualitative approach with observation and interviews, it was found that the principal implemented a democratic leadership style based on deliberation, which created a participatory work environment. However, a number of obstacles still confront teachers, such as limited technology, incompatibility of open fields, and ineffective time management. To overcome this, the principal conducted clinical supervision through the stages of planning, observation, and evaluation. The results showed an increase in teacher competence and learning quality. This study emphasizes the importance of participatory leadership and effective supervision in improving teacher professionalism in Islamic educational institutions. Keywords: Islamic Leadership, Clinical Supervision, Teacher Performance